Towards a better understanding of readmissions after stroke: partnering with stroke survivors and caregivers. Issue 7 (28th November 2014) - White, Carole L; Brady, Tracy L; Saucedo, Laura L; Motz, Deb; Sharp, Johanna; Birnbaum, Lee A
Abstract : Aims and objectives: To describe the experience of readmission from the perspective of the stroke survivor and family caregiver. Background: Older stroke survivors are at an increased risk for readmission with approximately 40% being readmitted in the first year after stroke. Patients and their families are best positioned to provide information about factors associated with readmission, yet their perspectives have rarely been elicited. Design: Descriptive qualitative study. Methods: This study included older stroke survivors who were readmitted to acute care from home in the six months following stroke, and their family caregivers. Participants were interviewed by telephone at approximately two weeks after discharge and a sub‐set was also interviewed in person during the readmission. Interviews were audio‐taped and content analysis was used to identify themes. Results: From the 29 semi‐structured interviews conducted with 20 stroke survivors and/or their caregivers, the following themes were identified: preparing to go home after the stroke, what to expect at home, complexity of medication management, support for self‐care in the community and the influence of social factors. Conclusions: This study provides the critical perspective of the stroke survivor and family caregiver into furthering our understanding of readmissions after stroke. Participants identified several areas for intervention including better discharge preparation and the need for support in the community for medication management and self‐care. The findings suggest that interventions designed to reduce readmissions after stroke should be multifaceted in approach and extend across the continuum of care. Relevance to clinical practice: The hospital level has been the focus of interventions to reduce preventable readmissions, but the results of this study suggest the importance of community‐level care. The individual nature of each situation must be taken into account, including the postdischarge environment and the availability of social support.